KUALITAS TEKS BERITA TULISAN MURID KELAS XI SMA NEGERI 1 UNGARAN DAN IMPLIKASINYA DALAM PEMBELAJARAN MENULIS TEKS BERITA - Sari, Santi Lufita; Herman Budiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the gap that occurs between the demands of learning to write news texts and students' actual abilities in producing texts that meet content and language standards. Problems found include incomplete 5W+1H elements, low information accuracy, and uneven application of language rules. This study aims to describe the level of fulfillment of content and language quality indicators of news texts written by grade XI students of SMA Negeri 1 Ungaran and formulate its implications for learning to write news texts. The method used is descriptive with a quantitative approach. The research data in the form of 27 news texts obtained through documentation techniques and analyzed based on indicators of content and language quality. The results show that the content quality reached a percentage of 73.7% with the fulfillment of the elements of what and who consistently, while the elements of when, where, why, and how did not appear evenly and the level of information accuracy was in the low category. Meanwhile, the language quality obtained a percentage of 26.2% which indicates that the application of language rules of news texts is inconsistent across texts. This finding confirms the need to strengthen learning that is oriented towards completeness of content, accuracy of information, accuracy of reverse structure, and consistency in the use of linguistic rules in news texts.